Fotobiomodulação associada ao tratamento conservador, na fase inicial, de pacientes com ruptura aguda do tendão do calcâneo: ensaio clínico randomizado duplo-cego - Oliveira, Pedro Rizzi de [UNIFESP] (2019)
Introduction: The Achilles tendon is the most affected by tendon ruptures, which is commonly related to sports practice. Immobilization in the conservative treatment leads to disorders on tendon tissue that can interfere in the tendon repair. Photobiomodulation (PBM) has been shown to be effective in promoting tissue repair and reducing the damages caused by immobilization. Objectives: Assess the effects of PBM associated with conservative treatment of patients with acute Achilles tendon rupture. Methods: Twenty-two male subjects, age between 18-65 years, with a diagnosis of acute rupture of the unilateral Achilles tendon performed by the Thompson test were included. Participants were randomly allocated into two groups: Control Group (CG) and Photobiomodulation Group (PBMG). Both groups underwent through a plaster immobilization protocol for 8 weeks. During this period, PBMG was submitted to 16 sessions of photobiomodulation (cluster 904nm, 858nm and 658nm) with the energy of 5 J per point and CG to a sham treatment. After the end of the plaster protocol both groups were submitted to the same protocol of rehabilitation for eight weeks, including strengthening exercises, proprioception and range of motion gain (ROM). The assessments were performed on 8th, 12th and 16 weeks, using the ATRS questionnaire, isometric dynamometry for plantar flexion, numeric pain scale (NPS) and goniometry of ankle joint. Results: Statistical difference (p <0.01) was found in favor of the PBMG in the NPS perceived in physical activity in the 12th week. No statistical differences were found in the ATRS questionnaire, muscle strength, ankle ROM. Conclusion: PBM did not has an effect on function, measured trough ATRS; FBM had an influence in reducing pain perceived at effort of patients with ruptured tendon of the calcaneus.